1982
DOI: 10.1021/bi00260a042
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of 1,3-diphosphoglycerate between glyceraldehyde 3-phosphate dehydrogenase and 3-phosphoglycerate kinase via an enzyme-substrate-enzyme complex

Abstract: On the basis of the alternatives of direct inter-enzyme transfer vs. dissociation followed by random diffusion, two kinetic models for metabolite transfer between consecutive enzymes are developed. These two models are readily distinguishable experimentally for the transfer of 1,3-diphosphoglycerate (1,3-P2G) between glyceraldehyde-3-phosphate dehydrogenase (GPDH) and 3-phosphoglycerate kinase (PGK). Since 1,3-P2G is exceedingly tightly bound to PGK, the kinetics of its transfer to GPDH are predictably differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 22 publications
1
65
2
Order By: Relevance
“…GAPDH was found to be distributed in muscle cytosol and the SR membrane, and ultrastructural localization studies have also revealed that GAPDH along with other glycolytic enzymes are bound to the cytoplasmic face of the SR membrane in skeletal muscle (33,38). A role for GAPDH together with 3-phosphoglycerate kinase (PGK) has been previously established in the production of ATP from GAP, NAD ϩ , P i , and ADP at the level of the SR membrane (19,20,39,40). In addition, a recent study demonstrated that synaptic vesicles were capable of generating local ATP via the membrane-associated GAPDH system, which could support the accumulation of the excitatory neurotransmitter glutamate even during significantly reduced global cellular ATP concentrations (41).…”
Section: Camentioning
confidence: 99%
“…GAPDH was found to be distributed in muscle cytosol and the SR membrane, and ultrastructural localization studies have also revealed that GAPDH along with other glycolytic enzymes are bound to the cytoplasmic face of the SR membrane in skeletal muscle (33,38). A role for GAPDH together with 3-phosphoglycerate kinase (PGK) has been previously established in the production of ATP from GAP, NAD ϩ , P i , and ADP at the level of the SR membrane (19,20,39,40). In addition, a recent study demonstrated that synaptic vesicles were capable of generating local ATP via the membrane-associated GAPDH system, which could support the accumulation of the excitatory neurotransmitter glutamate even during significantly reduced global cellular ATP concentrations (41).…”
Section: Camentioning
confidence: 99%
“…The activities of GAPDH and 3-PGK are energetically coupled, utilizing GAP, NAD, P i , and ADP, to yield 3-PG, ATP, NADH, and H ϩ (46,47). Because GAPDH is enriched in synaptic vesicles, we considered the possibility that 3-PGK may also preferentially localize to synaptic vesicle membranes.…”
Section: A 37-kda Protein Enriched In Synaptic Vesicles Is Labeled Wimentioning
confidence: 99%
“…2). Bernhard and co-workers (46,47) have demonstrated direct transfer of 1,3-BPG from GAPDH to 3-PGK in muscle tissue. Inhibition of vesicle-bound GAPDH activity by iodoacetate led to a reduction of ATP synthesis as well as to an attenuation of Glu uptake into synaptic vesicles (Fig.…”
Section: Atp Produced By Glycolysis Is Predominantly Utilized For Vesmentioning
confidence: 99%
“…Assuming that cE, > CL 9 k -ilk1 (6) the ligand will be present almost exclusively as the EIL complex after preincubation with El. The concentration of free ligand will then remain low ([L] < cL) also after subsequent addition of E2, such that Eqn (3) reduces approximately to (1). which gives With the additional assumption that both enzymes are used in large excess to ligand, Eqns (4) and (5) …”
Section: Kinetic Measurementsmentioning
confidence: 99%
“…The kinetic evidence for direct metabolite transfer reported by Weber and Bernhard [1] was based mainly on observed effects of phosphoglycerate kinase on the catalytic interaction of glyceraldehyde-3-phosphate dehydrogenase with bisphosphoglycerate and NADH. Our main approach has been to examine the kinetics of the two-enzyme system in the presence of NAD' instead of NADH.…”
Section: Mechanism Of Bisphosphoglycerate Transfer In the Binding Expmentioning
confidence: 99%